Endoscopy during the Covid-19 outbreak: experience and recommendations from a single center in a high-incidence scenario. Issue 6 (June 2020) - Elli, Luca; Rimondi, Alessandro; Scaramella, Lucia; Topa, Matilde; Vecchi, Maurizio; Mangioni, Davide; Gori, Andrea; Penagini, Roberto
Abstract: A dramatic SARS-Cov-2 outbreak is hitting Italy hard. To face the new scenario all the hospitals have been re-organised in order to reduce all the outpatient services and to devote almost all their personnel and resources to the management of Covid-19 patients. As a matter of fact, all the services have undergone a deep re-organization guided by: the necessity to reduce exams, to create an environment that helps reduce the virus spread, and to preserve the medical personnel from infection. In these days a re-organization of the endoscopic unit, sited in a high-incidence area, has been adopted, with changes to logistics, work organization and patients selection. With the present manuscript, we want to support gastroenterologists and endoscopists in the organization of a "new" endoscopy unit that responds to the "new" scenario, while remaining fully aware that resources, availability and local circumstances may extremely vary from unit to unit.